The 32 stops: The central line - Dorling, D (Penguin, 2013)
Geographer Danny Dorling tells the stories of the people who live along The 32 Stops of the Central Line to illustrate the extent and impact of inequality in Britain today - part of a series of twelve books tied to the twelve lines of the London Underground, as TfL celebrates 150 years of the Tube. Like the trace of a heartbeat on a cardiac monitor, the Central Line slowly falls south through west London, rises gently through the centre and then flicks up north through the east end of the capital. At the start of the journey life expectancy falls by two months a minute. Between the first four stations every second spent moving on the train is exactly a day off their lives in terms of how long people living beside the tracks can expect to live. By telling the personal stories of the very different people who live along the Central Line, the people who really make up The 32 Stops, geographer Danny Dorling explores the class and wealth divides that define our lives. His work shows the widening gap between rich and poor in the UK, and how where you live determines so much about your chances in life.